2009
DOI: 10.1038/jid.2009.142
|View full text |Cite
|
Sign up to set email alerts
|

IgA Anti-Epidermal Transglutaminase Antibodies in Dermatitis Herpetiformis and Pediatric Celiac Disease

Abstract: the manifestations of different forms of leprosy through their functional roles in antigen presentation and inhibition of T-cell responses.Although predisposing major histocompatibility complex alleles may exhibit inefficient antigen presentation, the LYP-Trp620 allele may have a pathogenic role in the hyporesponsiveness of T cells owing to anomalies in early T-cell signaling, resulting in clinical manifestations of leprosy. Contrary to our expectations, a significantly higher number of tuberculoid patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 3 publications
5
43
0
5
Order By: Relevance
“…Although DH patients may present with longterm severe intestinal disease, they tend to have a generally less severe form of celiac disease and tend to be diagnosed at a later age than celiac patients (24). IgA TG2 Abs are present in most DH patients (10,25,26). TG3 is also produced in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DH patients may present with longterm severe intestinal disease, they tend to have a generally less severe form of celiac disease and tend to be diagnosed at a later age than celiac patients (24). IgA TG2 Abs are present in most DH patients (10,25,26). TG3 is also produced in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA for human IgA and IgG TG3 and deamidated gliadin peptide ELISA was performed on seven selected DH patients and the seven control human sera as described previously (10). Sera were selected independent of patient disease activity, dapsone therapy, or adherence to gluten restriction in the diet.…”
Section: Patient Seramentioning
confidence: 99%
“…4,18,19,26 Serologic testing is a useful adjunct for diagnosis and may be used to monitor the therapy response. 29,34 Antigluten, antiendomysium, antigliadin and tTG antibodies have been detected in patients with DH, however, tTG and eTG are considered the target autoantigens in DH. 35 Heil et al 34 demonstrated that anti-tTG IgA can be useful for screening, because it is very disease-specific (100%) and sensitive (95% CD/96.6% DH) for the diagnosis of gluten sensitivity, while anti-eTG IgA was also very specific (100%), but was present in only 15% of CD cases and 44.8% of DH cases.…”
Section: Discussionmentioning
confidence: 99%
“…26 The tissue transglutaminase (tTG) was identified as the autoantigen prevalent in CD, 27 while in the DH, the predominant autoantigen is the epidermal transglutaminase (eTG). 26,28,29 Sardy et al 26 proposed that the DH pathogenesis consists of immune response of low avidity for tTG, resulting initially in silent CD, that with continued exposure to gliadin, leads to the development of populations of antibodies with high affinity to eTG for cross-reactivity, which manifests as DH. Moreover, as in CD, in which genetic predisposition is associated with the HLADQ2 (allelesDQA1 * 0501 and DQB1 *020) and HLA-DQ8 (DQA1 * 03 alleles and DQB1* 0302), DH presents similar genetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It is homologous to tissue TG within the enzymatically active domains and its main function in the epidermis to save the integrity of the skin. The expression of epidermal TG is primarily seen in the epidermis and small intestine (10,11).…”
Section: Introductionmentioning
confidence: 99%